Proposal of new postural positions for infants’ oral cleaning - Rank, Rise Iuata; Vilela, Joana Estela; Marquez, Luciana; Soares, Marília Pantoja; Sousa, Tatiane; Rank, Marcos; Ogawa, Wataro (REVISTA CEREUS, 2019)
The aim of this study was to propose to mothers two new postural positions to assist in the oral cleaning of infants up to 8 months of age and to verify their acceptance. The sample consisted of 38 mothers and their infants who participated in a program to promote oral health for children. The study consisted of 2 residential visits. In the first, a questionnaire was filled out by the mothers in order to know the habitual position in which the mother performed the hygiene of the baby's oral cavity and there was orientation with the new proposals for oral cleaning (Positions 1 and 2) . After 30 days, there was the return to verify which of the positions the mother preferred. Although the mothers received information about the baby's oral health, they weren’t told about an ideal postural position to perform oral cleaning. The diaper (86.8%) was the most used instrument, 31.5% found it difficult to clean the child's mouth, in which the majority of mothers reported being afraid of hurting the child during hygiene (91.6%). Position 1 was preferred for oral hygiene (p = 0.01), and of the reasons pointed out, proposal 1 was the easiest one (p = 0.04). All mothers adopted one of the new positions presented and position 1 was the most selected for oral hygiene in children.